Evaluation of Lipid Profile in Patients with Cherry Angioma: A Case-Control Study in Guilan, Iran - Abbas Darjani; Rana Rafiei; Sareh Shafaei; Elahe Rafiei; Hojat Eftekhari; Narges Alizade; Kaveh Gharaei nejad; Behnam Rafiee; Sara Najirad (Hindawi Limited, 2018)
Background. Cherry angioma is the most common type of acquired cutaneous vascular proliferation which would increase with aging due to some angiogenic factors but the exact pathogenesis is unknown. Usually angiogenic factors are synthesized in human body to compensate occlusive effects of atherogenic agents such as serum lipids. Our hypothesis was that increased levels of these angiogenic factors could be a trigger for development of cherry angioma. This study has been designed to compare frequency of dyslipidemia in subjects with and without cutaneous cherry angioma. Methods. In this case-control study, 122 cases with cherry angioma and 122 control subjects without cherry angioma were enrolled. Demographic characteristics, number of the cherry angioma lesions, and serum lipid profile were collected for all subjects. The data was analyzed using SPSS 18 software. Results. Mean levels of the total cholesterol, triglyceride, low-density lipoprotein, and high-density lipoprotein were higher in patients with cherry angioma compared to control subjects in which differences were significant for total cholesterol, low-density lipoprotein, and triglyceride (P<0.05) but not for high-density lipoprotein level. Conclusion. Serum lipids may have a role in producing angiogenic factors and development of cherry angioma and it seems logical to evaluate lipid profile in these cases.